PENDAMPINGAN PENGELOLAAN REKAM MEDIS DAN INFORMASI KESEHATAN DI PUSKESMAS CIBEUREUM KOTA TASIMALAYA TAHUN 2021 - idasugiarti; Arief Tarmansyah Iman; Fadil Ahmad Junaedi (APTIRMIKI, 2021)
Management of medical records and health information is one of the elements in the assessment of Public Health Center accreditation. Medical records play an important role in collecting accurate and comprehensive data for targeted health policies. The most appropriate management of medical records at the Public Health Center is the regional storage system or often referred to as the family folder system. Community service activities at the Cibeureum Health Center are carried out using consultation, training, and mentoring methods. Compiled 10 quality documents and the implementation of the e-family folder in stages. Furthermore, continuous data migration was carried out assisted by RMIK students. Activities carried out well.